Criminal justice system interactions among young adults with and without autism: A national birth cohort study in New Zealand. (October 2022) - Bowden, Nicholas; Milne, Barry; Audas, Richard; Clasby, Betony; Dacombe, Joanne; Forster, Warren; Kokaua, Jesse; Gibb, Sheree; Hughes, Nathan; MacCormick, Conrad; Smiler, Kirsten; Taylor, Barry; et al.
While sensationalist headlines and highly publicised criminal cases have led many to believe there is a link between autism and criminal behaviour, extant literature presents an unresolved debate. We sought to address this issue by examining the prevalence of criminal justice system interactions among young adults with and without autism, and by assessing whether offence types differ between these groups. This was a national birth cohort study using linked health and criminal justice system data. Cox proportional hazard models were employed to compare criminal justice system interactions between young adults with and without autism, controlling for important socio-demographic characteristics. Data were acquired for 1197 people with autism and 147, 879 without autism. Young adults with autism had significantly lower rates of being proceeded against by police, charged in court, and convicted in court compared to those without autism. However, those charged with an offence were significantly more likely to be charged with serious and violent offences, offences against the person and against property. Our findings indicate that, although young people with autism were not over-represented in the criminal justice system, disparities in offence types and incarceration rates among those charged with an offence suggest the importance of identification and appropriate response to autism within the criminal justice system. Lay abstract: Sensationalist headlines and highly publicised criminal cases lead many in the public to believe that people with autism are more likely to engage in criminal behaviour. However, recent studies present an unresolved debate, and indicate this may not necessarily be the case. The aims of this study were to examine the prevalence of criminal justice system interactions among young adults with and without autism, and determine whether offence types differ between these groups. We tracked a national birth cohort until their 25th birthday, detecting criminal justice system interactions from age 17 onwards. Linked health and criminal justice system data were used to identify those with autism and detect interactions with the criminal justice system. We found that young people with autism interacted with the criminal justice system at lower rates compared to those without autism. However, there were considerable differences in the types of offences these young people were charged with. For example, among those charged with an offence, people with autism were more likely to be charged with a serious offence, punishable by 2 or more years in prison. We conclude that although young people with autism are not over-represented in the criminal justice system, disparities in offence types and incarceration rates among those charged with an offence suggest the importance of identification and appropriate response to autism within the criminal justice system.